Development of Novel Guava Puree Films Containing Chitosan Nanoparticles - Lorevice, Marcos V.; Moura, Marcia R. de; Aouada, Fauze Ahmad [UNESP]; Mattoso, Luiz H. C. (Amer Scientific Publishers, 2012)
One of the overall goals of industries is to use packages that do not cause environmental problems at disposal time, but that have the same properties as the conventional ones. The goal of this study is to synthesize edible films based on hydroxypropyl methylcellulose (HPMC) with guava puree and chitosan (CS) nanoparticles. This was divided into two stages, the first is the synthesis of chitosan nanoparticles and the second is the production of the films. For the nanoparticles, average size and zeta potential measurements were performed. The characterizations of mechanical and thermal properties, solubility and water vapor permeability tests were conducted in the films. It was observed that when the nanoparticles were added to HPMC and guava puree films, they improved their mechanical and thermal properties, as well as decreased the films solubility and permeability. The potential application of the films prepared would be in edible films with flavor and odor to extend the shelf life of products.
Keywords: Edible Films; Hydroxypropyl Methylcellulose; Guava Puree; Chitosan Nanoparticles